Aged Refuse Recycling to Treat Wastewater from Coffee Processing - Nery del Carmen Rodiles-Cruz; Diego Alberto Ulloa-Gutiérrez; Rubén Fernando Gutiérrez-Hernández; Hugo Alejandro Nájera-Aguilar; Juan Antonio Araiza-Aguilar; Carlos Manuel García-Lara (Recycling)
Over the last two decades, the use of bioreactors filled with aged refuse extracted from closed areas of landfills has proven to be a viable alternative for the treatment of different types of wastewater. This study presents the results obtained during the evaluation of aged refuse used as filling material for a downflow bioreactor during the removal of the organic load present in wastewater generated in the wet processing of coffee. The tests were carried out over a period of 120 days, with 15 days to start up and stabilize the bioreactor and 105 days to perform treatability tests. The aged refuse, once extracted, was dried and sifted to a particle size of less than 50 mm. The bioreactor used had a cylindrical geometry (Ø = 0.20 m, and h = 3.40 m), and it was fed with hydraulic loads of 50, 100, and 150 L m−3 d−1. The analysis of the data obtained shows that the system studied achieves the removal of 98.3% of the initial organic load when fed with 150 L m−3 d−1. This showcases recycling aged refuse as a technically viable alternative to treat the wastewater generated during coffee processing. Also, the evaluated system has the advantage of needing a short period of time to achieve its stabilization, which turns out to be of great value, especially in its possible use in the treatment of residual water generated in the harvest of agricultural products where the period of harvest is very short.